Oxidative Aromatization of Pyrazolines - Casadia, Izamara; de Albuquerque, Danilo Y.; Carmo Capiotto, Adriana do; Pereira de Pereira, Claudio Martin; Pizzuti, Lucas (Current Organic Synthesis, 2017)
Background: Pyrazole derivatives have remained a much studied class of heterocyclic compounds with application in several scientific areas such as agrochemicals, pharmaceuticals and building blocks for more elaborated structures. The cyclocondensation of enones with hydrazine derivatives is one of the most valuable ways of synthesizing pyrazole derivatives. This method produces a racemic mixture of 4,5-dihydro- 1H-pyrazoles also known as pyrazolines which can be converted into aromatic pyrazoles by oxidative aromatization. Objective: The aim of this review article is to cover the state of the art oxidative aromatization of pyrazolines to pyrazoles. Method: It was performed a comprehensive compilation from the literature concerning the reported methods for oxidative aromatization of pyrazolines from the last thirty years. The review of each method was presented along with a critical point of view. Results: Several oxidant systems were applied for converting pyrazolines into pyrazoles. Most of the reviewed protocols proved to be efficient for oxidize 1,3,5-trisubstituted pyrazolines when the group attached to the N1 was H, methyl and (substituted)-phenyl. On the other hand few methods were found to dehydrogenate pyrazolines containing other than the above groups on N1 such as (thio)carbamoyl and amidinyl. Conclusion: Conversion of pyrazolines into aromatic pyrazoles by oxidative aromatization attracted attention in the last decades. A range of reagents has been reported for this purpose, but there is still the need for developing general methods that fill the requirements of green chemistry and that are applicable for more elaborated substrates.
Keywords: pyrazoles